Electronic Word Of Mouth (EWOM), Kepuasan Konsumen dan Pengaruh Langsung dan Tidak Langsung Terhadap Minat Beli Konsumen Online Shopee Pada Mahasiswa Di FEB Universitas Islam Malang - Nur Faiza; N. Rachma; M. Hufron (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACT This study aims to find out and analyze the electronic wprd ofmouth, consumer satisfaction and direct and indirect influence on the interest of Shopee Online Consumers on Students at FEB Malang Islamic University. The sample in this study was the FEB students of the Islamic University of Malang in the 2015-2018 academic year who had known 93 online shopee advertisements. Data collection is done by distributing questionnaires. The data analysis used in this study used validity, reliability, normality, path analysis, t test and sobel test.The results showed that Electronic word of mouth (EWOM) has a direct effect on customer satisfaction, Electronic word of mouth (EWOM) has a direct effect on social media, consumer satisfaction directly influences social media, electronic word of mouth (EWOM) has a direct influence on buying interest Social media has a direct effect on buying interest. Consumer satisfaction directly influences buying interest. Consumer satisfaction can mediate between Electronic word of mouth and social media. Social media can mediate between electronic word of mouth (EWOM) and buying interest, social media is not proven. can mediate between customer satisfaction with buying interest Keywords: EWOM, Consumer Satisfaction, Social Media, Buying Interest